Acute Myocardial Infarction Complicated by Cardiogenic Shock: An Algorithm‐Based Extracorporeal Membrane Oxygenation Program Can Improve Clinical Outcomes. Issue 3 (6th July 2015) - Unai, Shinya; Tanaka, Daizo; Ruggiero, Nicholas; Hirose, Hitoshi; Cavarocchi, Nicholas C.
Abstract: Extracorporeal membrane oxygenation (ECMO) in our institution resulted in near total mortality prior to the establishment of an algorithm‐based program in July 2010. We hypothesized that an algorithm‐based ECMO program improves the outcome of patients with acute myocardial infarction complicated with cardiogenic shock. Between March 2003 and July 2013, 29 patients underwent emergent catheterization for acute myocardial infarction due to left main or proximal left anterior descending artery occlusion complicated with cardiogenic shock (defined as systolic blood pressure <90 mm Hg despite multiple inotropes, with or without intra‐aortic balloon pump, lactic acidosis). Of 29 patients, 15 patients were treated before July 2010 (Group 1, old program), and 14 patients were treated after July 2010 (Group 2, new program). There were no significant differences in the baseline characteristics, including age, sex, coronary risk factors, and left ventricular ejection fraction between the two groups. Cardiopulmonary resuscitation prior to ECMO was performed in two cases (13%) in Group 1 and four cases (29%) in Group 2. ECMO support was performed in one case (6.7%) in Group 1 and six cases (43%) in Group 2. The 30‐day survival of Group 1 versus Group 2 was 40 versus 79% ( P = 0.03), and 1‐year survival rate was 20 versus 56% ( P = 0.01). The survival rate for patients who underwent ECMO was 0% in Group 1 versus 83% in Group 2 ( P = 0.09). In Group 2, the mean duration on ECMO was 9.8 ± 5.9 days. Of the six patients who required ECMO in Group 2, 100% were successfully weaned off ECMO or were bridged to ventricular assist device implantation. Initiation of an algorithm‐based ECMO program improved the outcomes in patients with acute myocardial infarction complicated by cardiogenic shock.